Peran Guru Dalam Meningkatakan Efektivitas Pembelajaran Kurikulum 13 Di SMP 2 Negeri Ambulu Kelas 8 - Ratna Amelia; Alfin Nur Laila; M. Aqil Mubarok; Moh. Ansori (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
In this abstract, we discuss the important role played by teachers in improving the performance of Curriculum 13 in Indonesia. Curriculum 13 Emphasizes project-based learning and scientific approaches to improve student competence. As the main role holder in the learning process, teachers have a big responsibility to design and implement learning in accordance with the principles of this curriculum. This research emphasizes how teachers use learning approaches that increase students' creativity, critical thinking, and social skills. In addition, discussions were held on supporting factors such as adequate training, availability of adequate resources, and support from school leadership to ensure that Curriculum 13 is implemented effectively in all schools.